2017
DOI: 10.1038/eye.2017.245
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and genetic testing for age-related macular degeneration

Abstract: Considerable advances have been made in our understanding of age-related macular degeneration (AMD) genetics over the past decade. The genetic associations discovered to date are estimated to account for approximately half of AMD heritability, and functional studies of these variants have revealed new insights into disease pathogenesis, leading to the development of potential novel therapies. There is furthermore growing interest in genetic testing for predicting an individual's risk of AMD and offering person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 102 publications
(120 reference statements)
0
43
0
4
Order By: Relevance
“…C3 has been shown to result in reduced binding to CFH and reduced complement regulation leading to increased membrane attack complex (MAC) deposition at the choriocapillaris [37,38]. The association of AMD pathogenesis with chromosome 10q26, which surrounds ARMS2 and HTRA1, has also been demonstrated in many studies although the debate is ongoing as to the causal allele and underlying pathogenic mechanism [39].…”
Section: Amd Pathogenic Mechanisms and Interaction Of Genetic/environmentioning
confidence: 99%
“…C3 has been shown to result in reduced binding to CFH and reduced complement regulation leading to increased membrane attack complex (MAC) deposition at the choriocapillaris [37,38]. The association of AMD pathogenesis with chromosome 10q26, which surrounds ARMS2 and HTRA1, has also been demonstrated in many studies although the debate is ongoing as to the causal allele and underlying pathogenic mechanism [39].…”
Section: Amd Pathogenic Mechanisms and Interaction Of Genetic/environmentioning
confidence: 99%
“…In einer kürzlich durch-geführten, genomweiten Assoziationsstudie (GWAS) wurden 52 häufige und seltene Genvarianten identifiziert, die unabhängig voneinander mit AMD assoziiert sind [108]. Unter ihnen befindet sich mehr als ein Drittel (19/52) in oder in der Nähe eines Komplementgens [103,105,108,109]. Insbesondere Varianten der Komplementgene CFH, CFI, C2/CFB, C3, C9, CD55 und Vitronectin (VTN) wurden mit einem erhöhten Risiko für die Entwicklung von AMD in Verbindung gebracht [108, 110 -112].…”
Section: Komplement-und Altersbedingte Makuladegeneration (Amd)unclassified
“…This observation has led to the hypothesis that rare TIMP3 protein-altering variants together with alleles at other AMD risk loci contribute to AMD development (Fritsche et al, 2016). A retrospective, observational case series has recently shown that patients initially diagnosed with neovascular AMD carry the SFD-associated p.(Ser38Cys)-TIMP3 mutation (Warwick & Lotery, 2017). SFD phenotypic expressivity varies considerably including large intra-and interfamilial variability in the age of onset of visual symptoms (Gliem, Muller, Mangold, Holz, et al, 2015).…”
Section: Mutati On S In Timp3mentioning
confidence: 99%